Georgia Architectural and Historic Properties Survey of Rural [074] North east section of county, Quitman, Ga. December 1980 - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Rural [074] North east section of county, Quitman, Ga. December 1980. 1 story irregularly shaped aluminum sided and vertical sided house with hipped and gabled roof. Square posts support surrounding shed porch. Modern windows. Interior chimneys. Excellent condition. Large oak & pecan trees. Date of Construction: Unknown. Typical rural house common to this area.
Georgia Architectural and Historic Properties Survey of Rural [074] North east section of county, Quitman, Ga. December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 2 scans. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 1.15 MB (1,211,811 bytes).
Keywords: Historic buildings; Real property surveys; Lowndes County Historical Society (Lowndes County, Ga.); Lowndes Co. (Ga.); Quitman (Ga.)